2009
DOI: 10.1002/bies.200800098
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome segment duplications in Neurospora crassa: barren crosses beget fertile science

Abstract: Studies on Neurospora chromosome segment duplications (Dps) performed since the publication of Perkins's comprehensive review in 1997 form the focus of this article. We present a brief summary of Perkins's seminal work on chromosome rearrangements, specifically, the identification of insertional and quasiterminal translocations that can segregate Dp progeny when crossed with normal sequence strains (i.e., T x N). We describe the genome defense process called meiotic silencing by unpaired DNA that renders Dp-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…located outside the duplicated segment) markers bracketed the ends of the duplicated (i.e. translocated) segment into progressively narrower intervals (often, < 10 kbp) (Vyas et al 2006;Singh et al 2009). Further delimitation of the junction intervals to 1-3 kbp was done by polymerase chain reaction (PCR) with oligonucleotide primers that anneal within these intervals; failure or success in PCR amplifi cation with translocation DNA template indicated whether or not the breakpoint lay between the primer binding sites (Singh et al 2009).…”
Section: Overview Of the Methods Used To Defi Ne The Breakpoint Junctimentioning
confidence: 99%
See 1 more Smart Citation
“…located outside the duplicated segment) markers bracketed the ends of the duplicated (i.e. translocated) segment into progressively narrower intervals (often, < 10 kbp) (Vyas et al 2006;Singh et al 2009). Further delimitation of the junction intervals to 1-3 kbp was done by polymerase chain reaction (PCR) with oligonucleotide primers that anneal within these intervals; failure or success in PCR amplifi cation with translocation DNA template indicated whether or not the breakpoint lay between the primer binding sites (Singh et al 2009).…”
Section: Overview Of the Methods Used To Defi Ne The Breakpoint Junctimentioning
confidence: 99%
“…It is possible that only a few of them are essential for meiosis and ascus development. Previous results from our laboratory have suggested that the silencing of Dp-borne genes might not be complete (Singh et al 2009), therefore the incomplete silencing of these few genes in a Dp(R2394)-heterozygous cross might not always result in barrenness. In contrast, Dp(UK8-18) duplicates 362 genes, therefore the incomplete penetrance of its barren phenotype is probably not due to an incomplete silencing of only a few ascus-essential genes.…”
Section: Non-barrenness Of Duplication-heterozygous Crosses Might Havmentioning
confidence: 95%
“…Duplications are likely to include one or more genes essential for meiosis and ascus formation and their presence in three copies in a duplication-heterozygous cross might cause one (or more) copy to not pair properly in meiosis, thus triggering silencing, and render the cross barren. The Sad-1, Sad-2 and Sms-2 semi-dominant suppressors of meiotic silencing can significantly (>100-1000Â) increase the productivity of Dp-heterozygous crosses (Shiu et al, 2001(Shiu et al, , 2006Lee et al, 2003;Singh et al, 2009). The Sad-1, Sad-2, and Sms-2 suppressor alleles are presumed to disrupt the normal pairing of their wild-type homologs (i.e., sad-1 + , sad-2 + , and sms-2 + ), and thereby induce them to silence themselves.…”
Section: Introductionmentioning
confidence: 98%
“…The unpaired genes are transcribed into 'aberrant RNA', which is processed into MSUD-associated small interfering RNA (masiRNA) used by the silencing complex to identify and degrade complementary mRNA as it exits the nucleus (Hammond et al 2013). Presumably, in a Dp-heterozygous cross, the Dp-borne genes, including those essential for the completion of meiosis and ascus development, fail to pair properly in meiosis and are silenced, thus rendering the cross barren (Singh et al 2009). But this does not explain the barrenness of Dp-homozygous crosses, in which all the genes are expected to be properly paired.…”
mentioning
confidence: 98%
“…Accumulation of extra transcripts from a duplicated segment might lower the editing levels of mRNA for Rid or other RIP proteins, and this might explain why in crosses heterozygous for a large Dp (i.e. >300 kbp), a smaller gene-sized duplication can escape RIP (Singh et al 2009). These possibilities now make it imperative to compare A-to-I RNA editing in N×N, Dp×N, and Dp×Dp crosses.…”
mentioning
confidence: 98%